Successional Stages of Mangroves in the Gulf of Kutch - Singh, H. S. (Indian Forester, 1996)
Mangroves of the west coast of India are mainly located in semi-arid zone of Gulf of Kutch in Gujarat where adverse climatic factors bring negative impact on the quality of forests and their floral diversity. The forests are exceptionally found in similar climatic condition in other parts of the world. Two species of Avicennia (Bhuradi and Makad) have occupied large area whereas low percentage of A. officinalis (Cher) is found in frontline. A. alba (Patcheradi) grows on higher mudflats. Micro climatic conditions in creeks on islands facilitate regeneration of Rhizophora, Ceriops and Ageiceros, Studies indicate that input of mud facilitates island expansion and shoreline propagation in the Gulf. Five distinct successional stages have been recorded in the mangroves on the islands in the Gulf where compostion of species in successional stages are governed by elevation of mud ground and water depth during high tides. All successional stages studied in the Gulf of Kutch towards Jamnagar are found in altitudinal range of approximately 190 cm and each level in this range bas different abiotic ecological factors. Each species found in the Gulf of Kutch prefers different elevation of intertidal mudflats resulting into distinct variation in composition of the mangroves in different successional stages. Classification of the stages in different levels in Jamnagar would be of immense use in selection of species for regenerating intertidal mudflats.